Treatment Plan for Ameloblastoma: A Review - Sthitaprajna Lenka1, Aditi Ava Rath2, Karishma Rathore3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Ameloblastoma is a tumor of odontogenic origin that exhibits 1% of all oral cavity tumors. Solid and multicysticare well chosen as locally aggressive, with elevated recurrence rates incase of conservative treatment.The objective of this review article is to analyze that the management of ameloblastoma should be doneconservatively or radically. The appropriate management of ameloblastoma should reduce reappearance,reinforce function and aesthetic, and exhibit a minimum damage in the donor area. Planning of the treatmentmust be done based on the extent,position, andtype of the lesion.